What's Past (and Present) Is Prologue: Interactions Between Justice Levels and Trajectories Predicting Behavioral Reciprocity. (April 2019) - Rubenstein, Alex L.; Allen, David G.; Bosco, Frank A.
Much of organizational justice research has tended to take a static approach, linking employees' contemporaneous justice levels to outcomes of interest. In the present study, we tested a dynamic model emphasizing the interactive influences of both justice levels and trajectories for predicting behavioral social exchange outcomes. Specifically, our model posited both main effects and interactions between present justice levels and past justice changes over time in predicting helping behavior and voluntary turnover behavior. Data over four yearly measurement periods from 4, 348 employees of a banking organization generally supported the notion that justice trajectories interact with absolute levels to predict both outcomes. Together, the findings highlight how employees invoke present fairness evaluations within the context of past fairness trends—rather than either in isolation—to inform decisions about behaviorally reciprocating at work.